Strijd om God: Om het behoud van de menselijke waardigheid - Coetsier, Meins G. S. (Tijdschrift voor theologie, 2009)
This article investigates the unrest that arises from the 'God-confusion'. The various personal experiences, insights and ways of symbolising divine reality in the present world - or lack thereof - have led to world-wide religious tensions and to a battle for God. This unrest has even led to fear and organised terrorism. In a culture characterized by an increasing surfeit of information, it is not easy to retain one's integrity, faith and morals. Are life, humanity and humaneness still consistent with religion? Richard Dawkins, Sam Harris, Christopher Hitchens and other representatives of a generation of radical atheists think not. They have launched a frontal attack against God and the Judeo-Christian tradition. This article primarily addresses Dawkins as a representative and symbol of the 'God-confusion'. In introducing German-American philosopher Eric Voegelin and Dutch Jewish writer Etty Hillesum, this article appeals against this popular-science distortion or mutilation of God. Voegelin's analysis of a pulverised God (in The Gospel and Culture) and Hillesum's personal reorientation toward the divine (in her Letters and Diaries) are invoked as possible answers to the present crisis of religion. In The God Delusion, Dawkins is fighting his battle against God - for atheism - over deformed 'God symbols', which of course says nothing about the experience of the divine, of the actual reality of God. Instead of focusing on real experiences, he initiates the reader into an ideological system. Unlike Dawkins, Voegelin and Hillesum have no difficulty with the notion of a 'God' or of a 'Holy Scripture'. Instead of creating a closed atheistic system, they turn to the experience of divine reality, which finds spontaneous expression in the symbol 'God' especially in Hillesum's writings. For Voegelin, the problem lies not in the experience of a divinity and/or spiritual reality, but in the dogmatising of this experience in ideologies and/or religious systems. Putting spiritual experiences into such systems has repeatedly led to bitterly disappointing results. So it is not surprising that the term 'God' elicits strongly sceptical responses in The God Delusion and elsewhere. It is by recalling and reviving the divine experience that we will be able to determine our own position in the current debate and to contribute to scientific investigations of God today.